Analysis of the Effect of Online-Based Interactive Digital Learning Media Word Wall on Pancasila and Citizenship Education Learning Outcomes of Elementary School Students - Umar Abdul Azis; Mubarak Ahmad (Universitas Pendidikan Mandalika, 2022)
This research aims to analyse the effect of online-based interactive digital learning media Word Wall on primary school student Pancasila and Citizenship Education learning outcomes. The method in this research used quantitative methods and quasi-experimental models with non-equivalent control group design. The research instrument used was test questions through pre-test and post-test. The data analysis technique used descriptive quantitative. The results of this research indicate that the interactive digital learning media Word Wall has an effect on improving student Pancasila and Citizenship Education learning outcomes as evidenced by statistical data from hypothesis testing using t-test with a significance value of 0.01 <0.05 and value of t-count > t-table which is 5.809 > 2.042. So, it can be said that the use of interactive digital learning media Word Wall in learning can improve the Pancasila and Citizenship Education learning outcomes of elementary school students.